Tinjauan Hukum terhadap Pembinaan Gelandangan Berdasarkan Prinsip Keadilan Sosial : Studi Kebijakan Dinas Sosial Kabanjahe - Putri Juliani Br Tarigan; Sri Hadiningrum (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the vagrancy rehabilitation policy implemented by the Social Service Office of Kabanjahe City from the perspective of social justice principles and to identify the factors contributing to the high number of vagrants in the area. The research employs a descriptive method with a normative-empirical approach, utilizing both primary data (interviews, observations, and documentation) and secondary data. The findings indicate that the vagrancy rehabilitation policy has a strong legal foundation, as stipulated in Article 34 paragraph (1) of the 1945 Constitution, Law No. 11 of 2009 on Social Welfare, and relevant regional regulations. Normatively, the policy aligns with the principle of social justice, which emphasizes equal opportunities and protection for vulnerable groups. However, its implementation still faces several challenges, including limited funding, insufficient social workers, inadequate facilities, and weak dissemination of program information. Consequently, the benefits of the rehabilitation program are unevenly distributed and have yet to effectively promote sustainable independence among the vagrant population.